1986
DOI: 10.1073/pnas.83.17.6622
|View full text |Cite
|
Sign up to set email alerts
|

Interferon enhances tryptophan metabolism by inducing pulmonary indoleamine 2,3-dioxygenase: its possible occurrence in cancer patients.

Abstract: Human lungs bearing cancer (n = 27) exhibited up to an "20-fold [on average "5-fold (P < 0.005)]increase in the enzyme activity that degrades tryptophan to form formylkynurenine, in comparison with lungs with benign lesions (blebs) (n = 7) taken as controls. On the basis of molecular and kinetic properties, this activity was ascribed to indoleamine 2,3-dioxygenase ()DO) [indoleamine:oxygen 2,3-oxidoreductase (decyclizing)]. In vitro studies with human lung slices revealed that human interferon y (IFN-y) induce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
118
0
14

Year Published

1990
1990
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 180 publications
(134 citation statements)
references
References 27 publications
2
118
0
14
Order By: Relevance
“…IllNo. 4 induced by viruses, bacterial exotoxins and interferona (24,54). It is mentioned, that IDO takes part in the elevated kynurenine formation in pathological as well as in host defence mechanisms (54).…”
Section: Pteridineslvol 11 Rnomentioning
confidence: 99%
“…IllNo. 4 induced by viruses, bacterial exotoxins and interferona (24,54). It is mentioned, that IDO takes part in the elevated kynurenine formation in pathological as well as in host defence mechanisms (54).…”
Section: Pteridineslvol 11 Rnomentioning
confidence: 99%
“…Essentially, IDO has been associated to peripheral tolerance and maternal tolerance towards the fetus. 2 Initial work of Musajo and Benassi 3 demonstrating increased urinary excretion of tryptophan metabolites of the kynurenine pathway in cancer patients followed by seminal work of Yasui et al 4 showing interferon γ (IFNγ)-mediated induction of IDO in lung cancer, paved the way for the more recent identification of increased expression of IDO by tumor cells 5 as well as for the attempts to clarify its possible role in tumor immune escape. 6 Mounting evidence indicates that, within the tumor microenvironment, not only tumor cells but also some subsets of tumor infiltrating cells, such as lymphocytes, dendritic cells and monocytes, can be sources of IDO.…”
Section: Introductionmentioning
confidence: 99%
“…However, KYNA is the NMDA-R antagonist (Perkins and Stone, 1982) and is protective against excitotoxicity of QUIN ( Kim and Choi, 1987). Therefore, the pro-inflammatory status in major depression would activate not only IDO (Carlin et al, 1987;Yasui et al, 1986) but also KMO enzyme activities (Mellor and Munn, 1999) and this might in turn shift the KYN metabolism to the 3HK and QUIN arm with possible reduction in KYNA (Figure-2). The changes in NMDA-R agonist and antagonist, QUIN and KYNA might have impact on glutamatergic neurotransmission.…”
Section: Interaction With Glutamatergic and Dopaminergic Neurotransmimentioning
confidence: 99%
“…The investigators reported the increased tryptophan and kynurenine in the brain of schizophrenia without evidence of generalized deficit in serotonin (Jospeh et al, 1979). After the discovery of the effect of pro-inflammatory cytokines on IDO enzyme activity (Carlin et al, 1987;Yasui et al, 1986) and the interaction between glucocorticoids and TDO activity (Knox, 1951;Nakamura et al, 1987;Salter and Pogson, 1985), the link between inflammatory state, tryptophan metabolism and serotonergic neurotransmission became of interest in the field of psychoneuroimmunology. Somehow, the report of a study on QUIN and kynurenine pathway metabolism in different inflammatory and non-inflammatory neurological diseases brought this field forward although it failed to show the significant association between metabolites in the CSF and psychiatric disorder such as depression (Heyes et al, 1992).…”
Section: Inflammation-tryptophan Metabolism-neurochemicals Interactionmentioning
confidence: 99%
See 1 more Smart Citation